Genome Sequence of Uric Acid-Fermenting Eubacterium angustum DSM 1989(T) (MK-1) - Poehlein, Anja (Genome Announc, 2017)
Eubacterium angustum DSM 1989(T) (MK-1) is a strictly anaerobic and uric acid-, xanthine-, and guanine-fermenting organism isolated from sewage sludge. The draft genome consists of one circular chromosome (2.4 Mb) and harbors 2,397 predicted protein-encoding genes.